Backstepping based adaptive finite-time tracking control of manipulator systems with uncertain parameters and unknown backlash. Issue 16 (November 2020) - Meng, Fanfeng; Zhao, Lin; Yu, Jinpeng
Abstract: In this paper, the adaptive finite-time command filtered backstepping control is investigated for uncertain manipulator systems with unknown backlash. The finite-time command filters, virtual control signal, adaptive update law and error compensation mechanism are designed respectively, which can deal with the computation complexity problem of conventional backstepping, and guarantee that the joint position tracking error reaches to a sufficiently small region including the origin in finite time although the uncertain parameters and unknown backlash are existed. The dynamic models of a two-link robot manipulator and the PUMA 560 manipulator are applied in simulation to verify the effectiveness of the given control strategy.